Strategies for Enhancing Courtyard Thermal Comfort in Hot Arid Phoenix: The Secret Garden on ASU Campus - Unal, Muge; Middel, Ariane (VDE VERLAG GMBH, 2025)
Courtyards possess unique geometric features that regulate sun exposure, wind, and humidity in hot climates. This study examines how surface materials and shading affect thermal comfort in courtyards in the hot arid climate of Phoenix, Arizona, through human-biometeorological observations and microclimate modeling. The Herberger Institute for Design and the Arts Hall (Secret Garden) on Arizona State University’s main campus were selected as case studies. The thermal environment of these courtyards was first evaluated for a typical hot and dry summer day in June 2023 using the ENVI-met 5.0.1 microclimate model. On-site measurements of key microclimatic variables, including air temperature (Ta), relative humidity (RH), wind speed (WS), and mean radiant temperature (MRT), were collected using the MaRTy platform to validate the model. Two scenario groups were then developed: the first tested various surface materials (concrete, grass, and water), and the second explored the impact of 3D vegetation configurations (central and bordered planting). Statistical analyses, including ANOVA and Tukey’s HSD tests, were conducted to compare the spatial differences in thermal exposure and comfort across the scenarios. © Wichmann Verlag, VDE VERLAG GMBH.
Keywords: Courtyard design; ENVI-met; heat mitigation strategies; MaRTy; microclimate